Wartości życia codziennego a sens życia – zmienne relacje - Mariański, Janusz (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2021)
This article presents a small selection of research issues related to everyday values as life goals and the relationship between everyday values and the meaning of life: at the macro-scale (adult Poles) and the micro-scale (Polish youth). Also quoted are selected research results from nationwide sociological surveys – conducted mainly by the Public Opinion Research Centre (CBOS) – and the results of selected sociological studies on young people in Poland. The supreme, ordering value, which to a noticeable extent dominates over the others, is family happiness and love. It seems that for many young people and adult Poles the discovered and declared sense of life is connected with more immediate goals, and fails to reach the metaphysical depth of the human existence. Affiliation values and the need for self-fulfilment through direct contact with people in small groups often turn out to be core values. When specific values are associated with multiple meanings, people find it difficult to create a coherent structure of the meaning of life.